2021
DOI: 10.1099/mic.0.001102
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free supernatants produced by lactic acid bacteria reduce Salmonella population in vitro

Abstract: The genus Salmonella is closely associated with foodborne outbreaks and animal diseases, and reports of antimicrobial resistance in Salmonella species are frequent. Several alternatives have been developed to control this pathogen, such as cell-free supernatants (CFS). Our objective here was to evaluate the use of lactic acid bacteria (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…It has been repeatedly confirmed that lactobacilli produce metabolites that suppress the growth of Salmonella [28][29][30]. Lactobacilli also produce metabolites affecting host gene expression [31,32].…”
Section: Discussionmentioning
confidence: 94%
“…It has been repeatedly confirmed that lactobacilli produce metabolites that suppress the growth of Salmonella [28][29][30]. Lactobacilli also produce metabolites affecting host gene expression [31,32].…”
Section: Discussionmentioning
confidence: 94%
“…plantarum 7.1 – nomenclature updated according to Zheng et al . [16] –, due to the bioprotective potential pointed out in several studies addressing the species [8, 17, 18]. The strains were stored in de Man, Rogosa, and Sharpe broth (MRS; HiMedia Laboratories, Mumbai, India) +20 % glycerol, in an ultrafreezer at −80 °C, and reactivated in 7 ml of MRS broth, incubated for 18 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…LAB were previously isolated from cocoa fermentation [15], with the selection of strains Limosilactobacillus (Lactobacillus) fermentum 5.2, Lactiplantibacillus (Lactobacillus) plantarum 6.2, and L. plantarum 7.1 -nomenclature updated according to Zheng et al [16] -, due to the bioprotective potential pointed out in several studies addressing the species [8,17,18]. The strains were stored in de Man, Rogosa, and Sharpe broth (MRS; HiMedia Laboratories, Mumbai, India) +20 % glycerol, in an ultrafreezer at −80 °C, and reactivated in 7 ml of MRS broth, incubated for 18 h at 37 °C.…”
Section: Bioprotective Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…We start this month with two papers from the Antimicrobials and AMR section of the journal. The first is from the group of Fernando Luciano at the Pontificia Universidade Catolica do Parana, Brazil [ 2 ]. This is an interesting paper that tests a potentially cheap approach to treat animal feed to reduce carriage of Salmonella in livestock.…”
mentioning
confidence: 99%